Comparison of ozone production by DBDP reactors: difference external electrodes. (February 2019) - Yulianto, E; Zahar, I; Zain, AZ; Sasmita, E; Restiwijaya, M; Kinandana, AW; Arianto, F; Nur, M
Abstract: Research on ozone generator performance technology of dielectric barrier discharge plasma (DBDP) has been conducted. The study was carried out by using two models of reactor configuration. The first model uses a wire mesh - aluminum foil configuration. The second model uses the wire mesh electrode configuration - wire mesh wrapped in aluminum foil. Ozone was generated using AC high Voltage. Oxygen that source of ozone has been taken from the water. The ozone was produced by DBDP reactor with voltage variation from 0.5 to 14 kV and a fixed air flow rate of 10 L / min. The first models of the reactor was Be Able to produce ozone of 138 ppm at a voltage of 14.3 kV with a maximum temperature of the inner reactor at 49 ° C. The second model of ozone produced with concentration of 163 ppm at a voltage of 14.2 kV and a maximum temperature of the inner reactor of 52 ° C. We found that reactor with wire mesh electrode configuration - wire mesh wrapped in aluminum foil can produce more high ozone concentration with the same voltage.